A systematic approach to understand hydrogeochemical dynamics in large river systems: Development and application to the River Ganges (Ganga) in India. (1st March 2022) - Richards, Laura A.; Fox, Bethany G.; Bowes, Michael J.; Khamis, Kieran; Kumar, Arun; Kumari, Rupa; Kumar, Sumant; Hazra, Moushumi; Howard, Ben; Thorn, Robin M.S.; Read, Daniel S.; Nel, Holly A.; et al.
Highlights: Systematic approach developed for hydrogeochemical understanding in large rivers. Longitudinal survey (> 2500 km) undertaken along river Ganga and key tributaries. Major hydrogeochemical zones and dominant processes determined at basin scale. Mixing, dilution and weathering are key processes controlling major hydrochemistry. Approach is transferable to other parameter types and/or other large river basins. Abstract: Large river systems, such as the River Ganges (Ganga), provide crucial water resources for the environment and society, yet often face significant challenges associated with cumulative impacts arising from upstream environmental and anthropogenic influences. Understanding the complex dynamics of such systems remains a major challenge, especially given accelerating environmental stressors including climate change and urbanization, and due to limitations in data and process understanding across scales. An integrated approach is required which robustly enables the hydrogeochemical dynamics and underpinning processes impacting water quality in large river systems to be explored. Here we develop a systematic approach for improving the understanding of hydrogeochemical dynamics and processes in large river systems, and apply this to a longitudinal survey (> 2500 km) of the River Ganges (Ganga) and key tributaries in the Indo-Gangetic basin. This framework enables us to succinctly interpret downstream water quality trends in response to the underpinning processes controlling major element hydrogeochemistry across the basin, based on conceptual water source signatures and dynamics. Informed by a 2019 post-monsoonal survey of 81 river bank-side sampling locations, the spatial distribution of a suite of selected physico-chemical and inorganic parameters, combined with segmented linear regression, reveals minor and major downstream hydrogeochemical transitions. We use this information to identify five major hydrogeochemical zones, characterized, in part, by the inputs of key tributaries, urban and agricultural areas, and estuarine inputs near the Bay of Bengal. Dominant trends are further explored by investigating geochemical relationships ( e.g. Na:Cl, Ca:Na, Mg:Na, Sr:Ca and NO3 :Cl), and how water source signatures and dynamics are modified by key processes, to assess the relative importance of controls such as dilution, evaporation, water-rock interactions (including carbonate and silicate weathering) and anthropogenic inputs. Mixing/dilution between sources and water-rock interactions explain most regional trends in major ion chemistry, although localized controls plausibly linked to anthropogenic activities are also evident in some locations. Temporal and spatial representativeness of river bank-side sampling are considered by supplementary sampling across the river at selected locations and via comparison to historical records. Limitations of such large-scale longitudinal sampling programs are discussed, as well as approaches to address some of these inherent challenges. This approach brings new, systematic insight into the basin-wide controls on the dominant geochemistry of the River Ganga, and provides a framework for characterising dominant hydrogeochemical zones, processes and controls, with utility to be transferable to other large river systems. Graphical abstract: Image, graphical abstract